Synergies in Child Nutrition : Interactions of Food Security, Health and Environment, and Child Care - Skoufias, Emmanuel (World Bank, Washington, DC, 2016)
This paper examines the extent to which the three key underlying determinants of nutrition -- food security; adequate caregiving resources at the maternal, household, and community levels; and access to health services and a safe and hygienic environment -- on their own and interactively are correlated with nutrition outcomes, such as height-for-age z-scores. Based on data from different years in eight countries in four regions where malnutrition is high, an indicator is constructed for each component of the three underlying drivers of nutrition. In spite of the limitations inherent in the available data, the analysis (i) reveals that progress toward improved access to adequate food security and adequate environment and health has been quite limited; and (ii) provides evidence of significant synergies among adequate food, child care, and environment and health.